EVALUATION OF INTERNAL AUDITING OF COOPERATIVES IN TURKİYE IN TERMS OF INTERNATIONAL REGULATIONS AND PRACTICES - GACAR, Anıl; YERELİ, Ayşe N. (SSD Journal, 2025)
Cooperatives, which are economic and social organizations that bring their members together for common goals, must establish an effective internal auditing structure in order to progress within the economic and social framework. When cooperatives in Türkiye are compared with international regulations and practices, both structural and legal deficiencies become evident. It is a fact that international regulations are more comprehensive and professional in this regard. In this study, the legal regulations concerning internal auditing of cooperatives in Türkiye are first explained through a comparison with international regulations. Then, the necessary components of an effective internal control system within the cooperative structure, along with related processes and practical implementations, are discussed. The shortcomings of current practices in Türkiye are identified, and solution proposals are developed accordingly.